PP.39.05: INVASIVE TREATMENT OF RENAL ARTERY STENOSIS 24-HOUR AMBULATORY OR OFFICE BLOOD PRESSURE MEASUREMENTS?. (June 2015) - Andersen, U.; Just, S.; Ibsen, H.; Bækgaard, N.; Brahm, M.
Abstract : Objective: Office blood pressure (OBP) is less well correlated to cardiovascular events than is 24 hour measurements (ABP). Nevertheless, ABP are rarely reported in studies of the effect of invasive treatment of renal artery stenosis. We report changes of ABP in 77 subjects that underwent balloon angioplasty and stenting (PTRA) in our center. We further report correlation to renal resisitive index (RI) measured before the procedure. Figure. No caption available. Design and method: The material consisted of 77 patients that underwent uni- or bilateral PTRA, and who had ABP before the procedure and after 3 months and one year. All ABP measurements were performed in our center using SPACELABS equipments The RI was measured by the same sonographer during the Doppler examinations of renal arteries, as mean of 3 measurements made in 3 segmental arteries. In case of differences between RI on the left and right side, the highest value was used. Results: ABP before vs after PTRA: Systolic 156 (19) vs 138 (17) mmHg (p < 0.00001), diastolic 85(13) vs 76 (10) mmHg (p < 0.0001). OBP before vs after PTRA: Systolic 162 (22) vs 147(23) mmHg (p < 0, 001), diastolic 89 (14) vs 80(14). In 24 cases, OBP were more than 15 mmHg higher than ABP, the highest difference being 54 mmHg. In 11 cases, OBP were more than 15 mmHg lower than ABP. Antihypertensive treatment reported as Defined Daily Doses (DDD) was 4.7 (2.6) vs 3, 4 (2.8) (p = NS). S-creatinin was 123 (46) vs 118 (40) μmol/l (P = NS). In 11 of 77 subjects with high RI (>80), the decrease of blood pressure after PTRA was smaller (11 vs 18 mmHg) and not signifikant. Conclusions: The decision of PTRA should be based on ABP, not OBP, since blood pressure in many instances grossly overestimated by OBP. The mean systolic ABP changed more than OBP in our cohort (15 vs 18 mmHg). There were no significant change of ABP in subjects with high RI.